Experimental Study on Temperature Measurement in Turning Operation of Hardened Steel (EN36). (2016) - Gosai, Mehul; Bhavsar, Sanket N.
Abstract: In metal cutting, the temperature measurement of cutting tool is being influenced by cutting factors, especially in continuous cutting operation. Since the life of the cutting tool material strongly depends upon cutting temperature, it is important to predict heat generation in tool with reliable techniques. In this study, cutting tool's average temperature was investigated by placing analog K-type thermocouple sensor in cutting tool. CNMG4325 Grade TN2000 Coated carbide insert with shim has been taken as cutting tool and round bar of EN36 hardened steel as work piece. The Data acquisition has been done with bridging of Amplifier and LabVIEW software through Arduino UNO R3 controller board. According to the mathematical model and equations, generated by CCD based RSM, experiments were performed and cutting temperature was obtained. Results have been analyzed and optimization has been carried out for selecting cutting parameters.